The prenatal diagnosis and genetic counseling of chromosomal micro-duplication on 10q24.3 in a fetus: A case report and a brief review of the literature. Issue 42 (16th October 2020) - Lai, Shaoyang; Zhang, Xueqin; Feng, Ling; He, Mengzhou; Wang, Shaoshuai
Abstract: Rationale: Split-hand/split-foot malformation (SHFM), also known as ectrodactyly, is a congenital limb malformation affecting the central rays of the autopod extending to syndactyly, median clefts of the hands and feet, aplasia/hypoplasia of phalanges, metacarpals and metatarsals. Duplication of this 10q24 region is associated with SHFM3. While the clinical and genetic heterogeneity of SHFM makes the prenatal diagnosis and genetic counseling more challenging and difficult. Patient concerns: A physically normal pregnant woman had a systemic ultrasound at the second trimester, only identified the deformity of both hands and feet on the fetus. Diagnoses: The fetus was diagnosed as sporadic SHFM3. Interventions: After seeking advice from genetic counseling, she decided to terminate the pregnancy. The induction of infant was done after appearance of bipedal clefts, lobster-claw appearance and partial loss of phalanges and metacarpals, leaving behind 2nd finger in the left hand and the 5th in the right hand. Furthermore, collection of umbilical cord is recommended to this fetus for genome-wide detection. Outcomes: An outcome of the gene detection from abortion shows that there is variation in copy number in genome of chromosome 1 and chromosome 10. Lessons: This case study confirms an association between SHFM3 and chromosomal micro-duplication on 10q24.3, and the extension of clinical spectrum of SHFM3. It also proposes some prenatal diagnosis and genetic counseling to help in planning and management in affected pregnancy. This will reduce the congenital and development abnormalities in birth rate, as well as relive the economic, psychological, and physical burden to the affected families.